2008
DOI: 10.1309/ajcpg4qzhlwfxmfj
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic Features of Metastatic and Recurrent Melanoma in Patients with Primary Cutaneous Desmoplastic Melanoma

Abstract: Desmoplastic melanoma (DM) is a rare subtype of melanoma characterized by malignant spindle cells associated with prominent fibrocollagenous stroma. Primary melanomas may be entirely desmoplastic ("pure" DM) or exhibit a desmoplastic component admixed with a nondesmoplastic component ("combined" DM). The cytologic features of only 5 cases of DM have been reported previously. Fine-needle biopsy (FNB) specimens from 20 recurrent or metastatic lesions in patients with cutaneous DM and 20 recurrent or metastatic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Metastases from primary pDMs less frequently involved lymph nodes than those from primary cDMs, which is in keeping with the documented lower incidence of lymph node involvement by DMs than by non‐DMs. In a recent study of the fine‐needle biopsy features of recurrent/metastatic DMs, we showed that pDMs contained spindle cells more often than cDMs, cDMs were more commonly composed of epithelioid cells than spindle cells, and bizarre/giant tumour cells were more frequently found in metastases of cDMs than in those of pDMs 17 . The findings in the present study of histological specimens are concordant with the previous cytological findings, and show that there is a strong correlation between the cellular composition and extent of desmoplasia (assessed as percentage desmoplasia and using the pDM/cDM classification) in the primary DM and in the metastases.…”
Section: Discussionmentioning
confidence: 86%
“…Metastases from primary pDMs less frequently involved lymph nodes than those from primary cDMs, which is in keeping with the documented lower incidence of lymph node involvement by DMs than by non‐DMs. In a recent study of the fine‐needle biopsy features of recurrent/metastatic DMs, we showed that pDMs contained spindle cells more often than cDMs, cDMs were more commonly composed of epithelioid cells than spindle cells, and bizarre/giant tumour cells were more frequently found in metastases of cDMs than in those of pDMs 17 . The findings in the present study of histological specimens are concordant with the previous cytological findings, and show that there is a strong correlation between the cellular composition and extent of desmoplasia (assessed as percentage desmoplasia and using the pDM/cDM classification) in the primary DM and in the metastases.…”
Section: Discussionmentioning
confidence: 86%
“…The presence of intracellular melanin pigment can be used as an important clue to the diagnosis which was present in approximately 80% of our cases. Recognizable melanin pigment is seen variably in the spindle cell variant [4,5,7,10,11,12,13,14,15,16]. It becomes more clinically challenging if spindle cells are present at metastatic sites such as lymph nodes, liver and spleen without an obvious clinical history of melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The first edition of The Art and Science of Cytopathology mentions the presence of vacuoles in Romanowsky‐stained FNA smears of melanoma and cites the paper by Gupta et al Interestingly, a Romanowsky‐stained smear in this text shows numerous cytoplasmic vacuoles, but these are not noted in the legend. Other texts and reports also included Romanowsky‐stained images of melanoma FNA smears showing cytoplasmic vacuoles but with no discussion of such in the legends and infrequent brief discussion in the report, which did not specify if vacuoles were present in Pap‐stained or Romanowsky‐stained smears . The second edition of The Art and Science of Cytopathology discusses the uncommon to rare balloon cell and signet‐ring cell variants of melanoma; however, no discussion was found regarding the presence of cytoplasmic vacuoles in FNA smears of routine melanomas .…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of cytoplasmic vacuoles in FNA smears of melanoma does not seem to be a generally recognized cytologic feature of melanoma, as we found minimal 4,5,15 to absent 3,8 discussion of such in major cytopathology texts, and with rare exception, 7 we found either no mention of, or minimal emphasis placed on this finding in published reports on the FNA cytology of melanoma. 1,2,6,[9][10][11][12][13][14]16 In this study, we test the theory that the presence of cytoplasmic vacuoles in FNA smears of melanoma is a common finding and, thereby, has potential utility in the cytologic diagnosis of melanoma.…”
Section: Abstract: Melanoma; Cytoplasmic Vacuoles; Fine-needlementioning
confidence: 99%